An unusual zig-zag 1D copper(ii) coordination polymer displaying magnetic phase transition. Issue 44 (25th October 2017) - Wang, Jun; Li, Bao-Hong; Lu, Lu; Liu, Jian-Qiang; Sakiyama, Hiroshi; Kumar, Abhinav
Abstract : A new Cu(ii )-based 1D chain was prepared and its magnetic behaviour was investigated, which indicated a magnetic phase transition below 25 K as well as long-range magnetic ordering. Abstract : An unusual Cu(ii ) coordination polymer [Cu(Him)2 (L)] (1 ) having a 4, 4′-{[1, 2-phenylene bis-(methylene)]bis(oxy)}dibenzoic acid ligand and an imidazole ligand possessing a 1D zig-zag chain was constructed and its magnetic behaviour was investigated, which indicated a magnetic phase transition below 25 K as well as long-range magnetic ordering.